Vitamins are Indeed Vital Amines: A Discussion of 3 Deficiencies With Neurologic Manifestations. (October 2021) - Tarhan, Bedirhan; Rahman, Sydur; Joseph, Nancy; Hyder, Douglas; Zingariello, Carla; Borum, Peggy R.; Sladky, John; Winesett, Steven Parrish
Optimal functioning of the human nervous system depends on a constant supply of nutrients, vitamins, and minerals. In the developed world, nutritional deficiencies are relatively rare and infrequently present with neurologic manifestations. These neurologic disorders can be mistaken for inflammatory and/or autoimmune phenomena. This manuscript describes 2 pediatric cases with neurologic signs/symptoms arising from vitamin deficiencies—(1) optic neuropathy and (2) Wernicke encephalopathy associated with a Guillain-Barre-like pattern of weakness. The 2 cases and the subsequent discussion of vitamin A, B1, and B12 deficiencies underscore the value of taking a thorough dietary history and emphasize risk factors for these 3 nutritional deficiencies.